(untitled) (Advances in Applied Mathematics and Mechanics, 2010)
Observations are reported on thermoplastic elastomer (ethylene-octene copolymer) melt in small-amplitude shear oscillatory tests and start-up shear tests with various strain rates in the interval of temperatures between 120 and 210 ^°C. Based on the concept of heterogeneous non-affine polymer networks, constitutive equations are developed for the thermo-mechanical behavior of a melt at three-dimensional deformations with finite strains. Adjustable parameters in the stress-strain relations are found by fitting the experimental data. The model is applied to the analysis of Poiseuille flow. The effects of temperature and pressure gradient on the steady velocity profile are studied numerically.